2015
DOI: 10.1039/c5ew00103j
|View full text |Cite
|
Sign up to set email alerts
|

The osmotic membrane bioreactor: a critical review

Abstract: The osmotic membrane bioreactor (OMBR) is a hybrid biological-physical treatment process for wastewater treatment and water reuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 153 publications
0
67
0
Order By: Relevance
“…A subsequent separation process, such as RO or membrane distillation, is often used for draw solute recovery and clean water production [9]. By employing a selective, semi-permeable FO membrane, various emerging TrOCs can be effectively retained in the bioreactor for further biodegradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent separation process, such as RO or membrane distillation, is often used for draw solute recovery and clean water production [9]. By employing a selective, semi-permeable FO membrane, various emerging TrOCs can be effectively retained in the bioreactor for further biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…Another promising approach to control salinity build-up in OMBR operation is to use ionic organic draw solutes as organic salts that diffuse into the bioreactor can be biodegraded by activated sludge [9,19,20]. However, with very few exceptions, ionic organic draw solutes have only been evaluated in FO applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, membrane fouling is less severe and more reversible than conventional MBR systems using either microfiltration (MF) or ultrafiltration [2,10]. OMBR can potentially be used as a stand-alone process to extract treated water for osmotic dilution [11], or integrated with other processes, such as membrane distillation (MD) [12] and nanofiltration (NF) or reverse osmosis (RO) [13][14][15], to recover the draw solute and produce clean water. In particular, coupling OMBR with MD can be an energy-efficient option as it allows for the utilisation of solar thermal or waste heat.…”
Section: Introductionmentioning
confidence: 99%
“…1). The first studies on OMBR-RO demonstrated interesting properties of the hybrid system: 8,9 (1) two successive dense membrane barriers for reliable production of high quality water, (2) low fouling propensity of OMBR, (3) low fouling in the RO step since the draw solution that must be concentrated is a clean stream (OMBR effluent), (4) no brine production (Fig. 1b).…”
Section: Where Can Osmotic Membrane Bioreactor Be Implemented In Watementioning
confidence: 99%
“…9 Significant improvement of osmotic pressure efficiency is required for OMBR to become competitive, i.e. by reaching similar operating flux as for MBR (at least 10 L m −2 h −1 ) while reducing significantly the osmotic pressure of the draw solutions (below 10 bar for standalone OMBR-RO) in order to limit energy costs for RO draw recovery.…”
Section: What Are the Necessary Ombr Improvements For Implementation?mentioning
confidence: 99%